Effects of multiple sessions of antimicrobial photodynamic therapy (aPDT) in the treatment of periodontitis in patients with uncompensated type 2 diabetes: A randomized controlled clinical study - Cláudio, Marina Módolo [UNESP]; Nuernberg, Marta Aparecida Alberton [UNESP]; Rodrigues, João Victor Soares [UNESP]; Belizário, Lícia Clara Garcia [UNESP]; Batista, Júlia Arruda [UNESP]; Duque, Cristiane [UNESP]; Garcia, Valdir Gouveia; Theodoro, Letícia Helena [UNESP] (Elsevier, 2021)
Background: The aim of this study was to compare, through clinical and microbiological analysis, the use of multiple applications of aPDT as an adjuvant therapy to non-surgical periodontal treatment of stage III and IV grade C periodontitis in type 2 diabetic (DM2) patients. Methods: Thirty-four patients with non-compensated DM2 and periodontitis were randomly divided into two groups: SRP Group (n = 17): scaling and root planing (SRP); and SRP+aPDT Group (n = 17): SRP followed by 3 consecutive aPDT applications, immediately, 48 and 96 h after in pockets with probing depth (PD) ≥5 mm. In SRP+aPDT, after 1 min of irrigation with methylene blue (10 mg/ml), the sites were irradiated with a 660 nm diode laser for 50 s (157 J/cm2, 4.7 J, 100 mW). Porphyromonas gingivalis (P. gingivalis) and Prevotella intermedia (P. intermedia) were quantified by real-time qPCR. Periodontal clinical and microbiological data (baseline, 90 and 180 days) were statistically analyzed (α = 5%). Results: There was a significant reduction in PD and bleeding on probing at 90 and 180 days post-treatment in both groups (p<0.05). The SRP+aPDT group presented a significant reduction in the number of residual pockets at 90 and 180 days (p<0.05). The SRP+aPDT group presented reduced PD means in deep pockets 180 days post-treatment (p<0.05). No differences were observed in P. gingivalis and P. intermedia levels (p>0.05). Conclusion: The results of present study indicate that the use of multiples aPDT sessions as adjuvant therapy in the periodontal treatment of uncompensated diabetic patients with periodontitis promotes additional clinical benefits.
Keywords: clinical trial; Dental scaling; Diabetes mellitus type 2; Periodontitis; Photodynamic Therapy